Effects of Authorial Voice on Literary Reception in the United States - Runny, Richard (American Journal of Literature Studies, 2024)
Purpose: The aim of the study was to assess the effects of authorial voice on literary reception in the United States. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicate that the tone, style, and perspective of the author can shape readers' interpretations and emotional responses to a text. For example, a confident and authoritative voice may engender trust and engagement, while a more experimental or ambiguous voice might provoke curiosity and critical reflection. Furthermore, readers' familiarity with an author's voice, whether through previous works or cultural reputation, can impact their expectations and predispositions towards new material. Implications to Theory, Practice and Policy: Reader-response theory, narrative theory and reception theory may be used to anchor future studies on assessing effects of authorial voice on literary reception in the United States. Encourage authors to actively engage with readers to solicit feedback on narrative voice choices and their impact on reader interpretation and enjoyment of literary works. Advocate for policies and initiatives that promote diversity and inclusion in literature, ensuring that marginalized voices and perspectives are represented and celebrated in the literary landscape.